40.2k views
1 vote
Solve for y
2y + 6 = 1 - 3y

2 Answers

4 votes

Answer:

y=−1

Explanation:

2y+6=1−3y

Step 1: Simplify both sides of the equation.

2y+6=1−3y

2y+6=1+−3y

2y+6=−3y+1

Step 2: Add 3y to both sides.

2y+6+3y=−3y+1+3y

5y+6=1

Step 3: Subtract 6 from both sides.

5y+6−6=1−6

5y=−5

Step 4: Divide both sides by 5.

y=−1

User Eparvan
by
5.2k points
3 votes

Answer:

-1

Explanation:

2y+6=1 -3y

add three to both sides and minus 6 from both sides becasue you want to get y by itself

5y=-5

now both sides by 5

y=-1

User Alex Ngo
by
5.4k points